2007
DOI: 10.1152/ajpheart.01079.2006
|View full text |Cite
|
Sign up to set email alerts
|

Modified LDLs induce proliferation-mediated death of human vascular endothelial cells through MAPK pathway

Abstract: Apostolov EO, Basnakian AG, Yin X, Ok E, Shah SV. Modified LDLs induce proliferation-mediated death of human vascular endothelial cells through MAPK pathway. Am J Physiol Heart Circ Physiol 292: H1836 -H1846, 2007. First published December 22, 2006; doi:10.1152/ajpheart.01079.2006.-The ability of modified low-density lipoptoteins (LDLs) to induce both proliferation and death of endothelial cells is considered to be a mechanism of early atherosclerosis development. We previously showed that carbamylated LDL (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 48 publications
6
35
0
1
Order By: Relevance
“…9,[13][14][15][16] Among those, the role of the intercellular adhesion molecule 1 (ICAM-1) and monocyte adhesion by endothelium were most prominent and, in some conditions, exceeded those induced by oxLDL. 13 To test whether ICAM-1 overexpression and macrophage housing occurred in vivo as a result of uremic atherosclerosis associated with LDL carbamylation, the aortic samples were simultaneously stained for cLDL and for ICAM-1 or CD68, respectively.…”
Section: Brief Communication Wwwjasnorgmentioning
confidence: 99%
See 1 more Smart Citation
“…9,[13][14][15][16] Among those, the role of the intercellular adhesion molecule 1 (ICAM-1) and monocyte adhesion by endothelium were most prominent and, in some conditions, exceeded those induced by oxLDL. 13 To test whether ICAM-1 overexpression and macrophage housing occurred in vivo as a result of uremic atherosclerosis associated with LDL carbamylation, the aortic samples were simultaneously stained for cLDL and for ICAM-1 or CD68, respectively.…”
Section: Brief Communication Wwwjasnorgmentioning
confidence: 99%
“…cLDL promotes several biologic processes in vitro that are regarded as pro-atherogenic, including vascular smooth muscle cell proliferation, monocyte adhesion to endothelial cells, 13,14 and endothelial cell cytotoxicity. 9,15,16 However, experimental evidence showing a pro-atherogenic effect of cLDL in vivo is lacking. To obtain this critical evidence, we established two mouse models of elevated plasma urea using (1) a standard model of surgical kidney reduction that mimics CRF in humans 17 and (2) a newly developed, urea consumption (UC) model that elevates plasma urea independently of renal failure.…”
mentioning
confidence: 99%
“…13 Our recent study showed that cLDL induced a variety of damaging stimuli to endothelial and vascular smooth muscle cells, all of which are attributed to atherosclerosis. 10,14 These include incorporation by endothelial cells, cytotoxicity toward endothelial cells, and the induction of vascular smooth muscle cell proliferation.…”
mentioning
confidence: 99%
“…20 It has been reported that modified LDL (oxidated, glycated) can induce p38 MAPK transient activation in different cell types. [35][36][37][38] However, the significant decrease in pHSP27, below control levels, after 24 hours of treatment with LDL is neither related to p38 MAPK activity nor to MAPKAPK2. LDL-related dephosphorylation of HSP27 is not due to the switch-off of MAPK but to a counterregulation by PPA2, 39 because inhibition of PPA2 by either OA or fostriecin blocked the effect of LDL on pHSP27.…”
Section: Discussionmentioning
confidence: 92%